(untitled) (Baghdad Science Journal, 2006)
I attended some amides non grassy substitutes such as acrylic compounds Amaid Electron Amaid and Alsinamamaid interaction unsaturated acids such as acrylic acid or Ketronk ????????? with primary amines Malkhtlfah of acrylic monomers Alamayd